The Development of Hapanasan Hot Spring Nature Tourism in Rokan Hulu, Riau, Using the Analysis Hierarchy Process (AHP) - Rahmawaty; Kholizah, Siti; Harahap, Hamdani; Ismail, Mohd Hasmadi (Journal of Environmental and Development Studies, 2023)
Hapanasan hot spring, located in Rokan Hulu Regency, Riau Province, is a natural tourist destination with high potential. Despite its potential, the resource utilization carried out by the community and local government is not yet fully developed. This study aims to analyze the priority factors for developing Hapanasan hot spring. This study collects primary data by observing the area and conducting Forum Group Discussions (FGD). Secondary data was obtained from document studies applied to various data sources such as the Tourism Office, Regional Development Planning Agency, and Non-Governmental Organizations. The method used in this study is the Analytical Hierarchy Process (AHP), and the data is processed with expert choice software. Based on the results of the AHP and the software analysis, the priority for developing natural hot spring tourism in Hapanasanis in the criteria for aspects of tourist objects and attractions with a value of 0.438, while the sub-criteria for the structure of natural tourism is improving facilities and infrastructure with a value of 0.869, and there is an alternative in the form of increasing the capacity of elements of facilities and infrastructure with a value of 0.290.